First-principles calculations of oxygen interstitials in corundum: A site symmetry approach - Evarestov, Robert A.; Platonenko, Alexander; Gryaznov, Denis; Zhukovskii, Yuri F.; Kotomin, Eugene A. (Royal Society of Chemistry, 2017)
Using site symmetry analysis, four possible positions of interstitial oxygen atoms in the α-Al2O3 hexagonal structure have been identified and studied. First principles hybrid functional calculations of the relevant atomic and electronic structures for interstitial Oi atom insertion in these positions reveal differences in energies of ∼1.5 eV. This approach allows us to get the lowest energy configuration, avoiding time-consuming calculations. It is shown that the triplet oxygen atom is barrierless displaced towards the nearest regular oxygen ion, forming a singlet dumbbell (split interstitial) configuration with an energy gain of ∼2.5 eV. The charge and spatial structure of the dumbbell is discussed. Our results are important, in particular, for understanding the radiation properties and stability of α-Al2O3 and other oxide crystals.
The authors are indebted to R. Vila, A. Popov and A. Lushchik for stimulating discussions. This work was carried out within the framework of the EUROfusion Consortium and received funding from the European Union’s Horizon 2020 Research and Innovation Programme under grant agreement 633053. The views and opinions expressed herein do not necessarily reflect those of the European Commission. Support from Latvian National Research Program IMIS2 (2014–2017) is also appreciated. Calculations were carried out using both the Marconi supercomputer system at the Computational Simulation Centre and the Computer Center of St. Petersburg State University.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics